1992
DOI: 10.1002/zoo.1430110203
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen metabolism in the Asian elephant (Elephas maximus)

Abstract: Estradiol-17P metabolism was studied in two female Asian elephants (Elephas maximus). In an initial study, 500 pCi of tritiated estradiol-17P was injected iv into a single animal, and 0, 30 and 60 min serum samples were collected as well as all excreted urine and feces for 24 hr. In a second study, 1.5 mg unlabeled estradiol-17P was injected iv into a second animal and 0, 5 , 15, 30, and 60 min serum samples and a 30 min urine sample were collected postinjection. Analyses of samples from both studies demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Although fecal monitoring has been used in other avian species to measure daily changes in sex steroid production [Bishop and Hall, 1991;Yamaguchi and Ishii, 1991;Cockrem and Rounce, 1994;Lee et al, 1995], the present data are the first to demonstrate that daily fecal/urine measurements reflect primarily the excretion products of estradiol and testosterone produced during the previous 24 hr. These results are unlike mammalian studies in which radiolabeled steroid excretion has been relatively slow and overall recovery has been low [Shille et al, 1984;Loskutoff et al, 1987;Ziegler et al, 1989;Hindle and Hodges, 1990;Czekala et al, 1992;Shideler et al, 1993]. The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection.…”
Section: Discussioncontrasting
confidence: 83%
“…Although fecal monitoring has been used in other avian species to measure daily changes in sex steroid production [Bishop and Hall, 1991;Yamaguchi and Ishii, 1991;Cockrem and Rounce, 1994;Lee et al, 1995], the present data are the first to demonstrate that daily fecal/urine measurements reflect primarily the excretion products of estradiol and testosterone produced during the previous 24 hr. These results are unlike mammalian studies in which radiolabeled steroid excretion has been relatively slow and overall recovery has been low [Shille et al, 1984;Loskutoff et al, 1987;Ziegler et al, 1989;Hindle and Hodges, 1990;Czekala et al, 1992;Shideler et al, 1993]. The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection.…”
Section: Discussioncontrasting
confidence: 83%
“…Alternatively, it is possible that the elephant ovary secretes estrogen metabolites other than estradiol, as has been shown for progestogens, for which the most abundant circulating forms are 5␣-reduced compounds, not progesterone [25][26][27]. There is evidence that circulating estradiol may predominate in a conjugated form, rather than a free steroid form, in both Asian [28] and African [29] elephants. However, incubation of Asian elephant serum with ␤-glucuronidase/aryl sulfatase to hydrolyze estrogen conjugates before analysis did not provide any clearer evidence of cyclic follicular activity (unpublished results).…”
Section: Discussionmentioning
confidence: 96%
“…It is notable that such a clear pattern emerges using a urinary estrogen conjugate assay when earlier attempts to assess estrogen dynamics using serum analyses failed to show any relationship with elephant reproductive status [for reviews see Hodges, 1998;Brown, 2000]. One possible reason for the inconclusive serum results is that the free steroid is quickly metabolized to estradiol and estrone conjugates in the bloodstream [Czekala et al, 1992]. Thus, techniques to measure circulating estradiol would have excluded the identification of a conjugated form due to the extraction process.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a reliable serum indicator of follicular activity led to the investigation of urinary estrogen analysis as a possible alternative, the biological relevance of which was based on radiolabel infusion studies that showed circulating estrogen conjugates are excreted primarily (95%) in the urine of Asian [Czekala et al, 1992] and African [Wasser et al, 1996] elephants. However, urinary estrogen data have also been inconsistent, likely because of sampling frequency limitations.…”
Section: Discussionmentioning
confidence: 99%